Cost consequences analysis of hypertensive outpatients: a study in a private hospital in Yogyakarta special province - Dinasari Bekti Pratidina; Fithria Dyah Ayu Suryanegara; Diesty Anita Nugraheni (Jurnal Ilmiah Farmasi, 2021)
Abstract  Background: Hypertension is a chronic disease that requires long-term treatment and has an impact on the cost of treatment. The costs will be greater given the loss of productivity, family burden, and social life impacted by hypertension based on patient’s perspective.Objective: The purpose of the study was to determine the costs and clinical outcome of antihypertensive therapy from the patient's perspective and to identify the discrepancies between the costs and the INA-CBGs (Indonesia Case Based Groups) tariff.Methods: The research was an observational study with a cross-sectional design. The targeted population was outpatients who had received antihypertensive therapy for at least 1 month at a private hospital in Yogyakarta. The costs included direct medical costs, direct non-medical costs, and indirect costs, while the clinical outcomes were patient’s blood pressure. The descriptive analysis was carried out to describe the characteristics of the research subjects, the clinical outcome, and the cost. Analysis of the discrepancies between the costs and the INA-CBGs tariff used the Mann-Whitney test and One-Sample t-test.Results: The results showed that the average direct medical costs, direct non-medical costs, and indirect costs from the patient’s perspective were IDR359,408.00, IDR24,617.00, and IDR 40,583.00, respectively. There was a significant difference between the real costs and the rate of INA-CBGs based on the results of statistical tests, while the cost discrepancy was IDR5,287,045.00.Conclusion: The direct non-medical costs and indirect costs of hypertensive outpatients were less than the direct medical costs.  A significant difference occurred between the real costs and INA CBG’s tariff.Keywords: hypertension, cost consequences, pharmacoeconomics, patient’s perspectiveIntisari  Latar belakang: Hipertensi termasuk penyakit kronis yang membutuhkan waktu pengobatan panjang dan biaya besar. Biaya akan lebih besar karena pasien kehilangan produktivitas, beban pada kehidupan keluarga dan masyarakat akibat penyakit hipertensi berdasarkan perspektif pasien.Tujuan: Penelitian bertujuan untuk mengetahui gambaran biaya dan outcome terapi antihipertensi berdasarkan perspektif pasien serta kesesuaian biaya riil dengan tarif INA-CBGs.Metode: Desain penelitian adalah observasional dengan rancangan cross-sectional. Populasi penelitian adalah pasien hipertensi rawat jalan di satu rumah sakit swasta Yogyakarta yang menerima terapi antihipertensi selama minimal 1 bulan. Analisis deskriptif digunakan untuk menggambarkan karakteristik subjek penelitian, outcome terapi, dan biaya terapi. Analisis kesesuaian biaya riil  dengan tarif INA-CBGs dengan uji statistik Mann Whitney dan One Sample t-test.Hasil: Hasil penelitian menunjukkan rata-rata biaya langsung medis, biaya non medis langsung, dan biaya tidak langsung berdasarkan perspektif pasien berturut-turut adalah Rp.359.408,00; Rp.24.617,00; dan Rp.40.583,00. Outcome terapi tertinggi ditunjukkan antihipertensi tunggal Calcium Channel Blocker (CCB) (60%). Terdapat perbedaan secara statistik antara biaya riil dengan tarif INA-CBGs (p=0,009 dan p=0,004) dan selisih biaya sebesar (Rp.5.287.045,00).Kesimpulan:Biaya nonmedis langsung dan biaya tidak langsung pasien hipertensi rawat jalan tidak sebesar biaya medis langsung. Perbedaan signifikan antara biaya riil dan tarif INACBG’s menjadi bahan evaluasi perbaikan tarif INACBG’s bagi BPJS Kesehatan. Hasil tersebut juga memicu pihak rumah sakit untuk melakukan evaluasi terhadap clinical pathway agar dapat memberikan terapi yang lebih efektif dan efisien.Kata kunci: hipertensi, cost consequences, farmakoekonomi, perspektif pasien